Edukasi Green Marketing untuk Meningkatkan Kesadaran Konsumen terhadap Produk Ramah Lingkungan dalam Upaya Mendukung Kesehatan Lingkungan: Pengabdian - Afnina; Yulina Astuti; Nurlaila Hanum; Krisniawati; Susanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program aims to increase consumer awareness of environmentally friendly products through green marketing education in East Aceh. This activity was motivated by the problem of accumulated and underutilized palm frond waste, as well as low public awareness of choosing environmentally friendly products, coupled with limited production, packaging, and digital promotion skills among local business actors. The program was carried out using a participatory approach through the stages of preparation, socialization, training, digital marketing implementation, and evaluation. The results showed significant improvements: green marketing knowledge increased from 38% to 88%, skills in processing palm waste into environmentally friendly products from 30% to 85%, packaging and digital promotion skills increased by more than 50%, and consumer awareness of choosing environmentally friendly products from 35% to 84%. This proves that green marketing education is effective in increasing consumer understanding, skills, and awareness, while helping to reduce waste, open new economic opportunities, and support sustainable development.